Effect of Age and Level of Income on Income Tax Compliance Among Small and Medium Enterprises in Soroti District, Uganda - Otai, Isaac Peter; Ndede, Fredrick W S; Fredrick, Warui Waweru (Archives of Business Research, 2023)
This study, investigated whether or not there is a relationship between age, level of income and income tax compliance among Small and Medium Enterprises in Soroti district in Uganda. The objectives of the study were to; find out the relationship between age of owner/manager on income tax compliance and to determine the relationship between level of income on income tax compliance by Small and Medium Enterprises in Soroti District, Uganda. A sample of 384 respondents was selected from a population of 2590 owners/managers of small and medium firms using stratified random sampling technique. A semi-structured questionnaire was used to collect primary data which were coded into Statistical Package for Social Scientists for descriptive analysis. One way Analysis of Variance as well as correlation and logistic regression were carried out. The study findings were that; age of owner manager of the firms have a significant relationship with income tax compliance by the firms. However, the level of income was found not to have a relationship with income tax compliance among the firms. The study concluded that, differences in age significantly explain income tax compliance decisions of owners/managers.